Changes in albumin-to-creatinine ratio at 12-month follow-up in patients undergoing renal denervation - Henrique Sousa; Patrícia Branco; Manuel de Sousa Almeida; Pedro de Araújo Gonçalves; Augusta Gaspar; Hélder Dores; João Mesquita; Maria João Andrade; Nuno Neuparth; Ana Aleixo; Miguel Mendes; José Diogo Barata (Revista Portuguesa de Cardiologia, 2017)
Introduction: Sympathetic renal denervation (RDN) was developed as a treatment for the management of patients with resistant hypertension. This procedure may have a positive impact on hypertension-related target organ damage, particularly renal disease, but the evidence is still limited. Objective: To assess the impact of RDN on the albumin-to-creatinine ratio (ACR) at 12-month follow-up. Methods and Results: From a single-center prospective registry including 65 patients with resistant hypertension undergoing renal denervation, 31 patients with complete baseline and 12-month follow-up blood pressure (BP) measurements (both office and 24-h ambulatory blood pressure monitoring [ABPM]) and ACR were included in the present study. Mean age was 65±7 years, 52% were female, most (90%) had been diagnosed with hypertension for more than 10 years, 71% had type 2 diabetes and 33% had vascular disease in at least one territory. Mean estimated glomerular filtration rate was 73.6±25.1 ml/min/1.73 m2 and 15 patients (48%) had an ACR >30 mg/g. After 12 months, 22 patients were considered BP responders (73%). ACR decreased significantly from a median of 25.8 mg/g (interquartile range [IQR] 9.0-574.0 mg/g) to 14.8 mg/g (IQR 4.5-61.0 mg/g, p=0.007). When the results were split according to systolic BP responder status on ABPM, we found a significant reduction in responders (from 25.6 mg/g [IQR 8.7-382.8 mg/g] to 15.9 mg/g [IQR 4.4-55.0 mg/g], p=0.009), and a numerical decrease in the non-responder subgroup (from 165.0 mg/g [IQR 8.8-1423.5 mg/g] to 13.6 mg/dl [IQR 5.7-1417.0 mg/g], p=0.345). Conclusions: Besides significant reductions in blood pressure (both office and 24-h ABPM), renal denervation was associated with a significant reduction in ACR, a recognized marker of target organ damage. Resumo: Introdução: A desnervação simpática renal (RDN) foi desenvolvida como uma forma de tratamento para os doentes com hipertensão arterial resistente (R-HTN). Este procedimento poderá ter um impacto favorável nas lesões de órgão alvo relacionadas com a hipertensão, nomeadamente a doença renal, no entanto, a evidência disponível ainda é escassa. Objetivo: Avaliar o impacto da RDN no rácio albumina-creatinina (ACR) aos 12 meses de seguimento após RDN. Métodos e resultados: Registo prospetivo de centro único incluindo 65 doentes com R-HTN submetidos a RDN, dos quais 31 doentes com avaliação basal e a um ano completa da pressão arterial (na consulta e na monitorização ambulatória [ABPM]) e da ACR foram incluídos no presente estudo. A idade média foi de 65±7 anos, 52% do sexo feminino. A maioria da população tinha diagnóstico de HTN há >10 anos, 71% tinha diabetes tipo 2 e 33% tinham doença vascular em pelo menos um território. A taxa de filtração glomerular estimada foi de 73,6±25,1 ml/min/1,73 m2 e 48% (15 doentes) tinham uma ACR>30 mg/g. Aos 12 meses de seguimento, 22 doentes foram considerados respondedores na pressão arterial (73%). A ACR teve uma descida significativa de uma mediana de 25,8 mg/g (IQR 9,0-574,0 mg/g) para 14,8 mg/g (IQR 4,5-61,0 mg/g, p=0,007). Quando os resultados foram divididos em subgrupos, de acordo com o estado de respondedor à pressão arterial na ABPM, verificou-se uma redução significativa nos respondedores (de 25,6 mg/g [IQR 8,7-382,8 mg/g] para 15,9 mg/g [IQR 4,4-55,0 mg/g], p=0,009), e uma tendência no subgrupo de não respondedores (de 165,0 mg/g [IQR 8,8-1423,5 mg/g] para 13,6 mg/dl [IQR 5,7-1417,0 mg/g], p=0,345). Conclusão: Para além da descida significativa da pressão arterial (quer na consulta quer na monitorização ambulatória de 24 h), a desnervação renal associou-se a uma redução significativa da ACR, um reconhecido marcador de lesão de órgão alvo na hipertensão arterial. Keywords: Resistant hypertension, Renal denervation, Albuminuria, Blood pressure, Palavras-chave: Hipertensão arterial resistente, Desnervação renal, Albuminúria, Pressão arterial